Viral Load Drives Disease in Humans Experimentally Infected with Respiratory Syncytial Virus - DeVincenzo, John P. (American Thoracic Society, 2010)
Rationale: Respiratory syncytial virus (RSV) is the leading cause of childhood lower respiratory infection, yet viable therapies are lacking. Two major challenges have stalled antiviral development: ethical difficulties in performing pediatric proof-of-concept studies and the prevailing concept that the disease is immune-mediated rather than being driven by viral load. Objectives: The development of a human experimental wild-type RSV infection model to address these challenges. Methods: Healthy volunteers (n = 35), in five cohorts, received increasing quantities (3.0–5.4 log plaque-forming units/person) of wild-type RSV-A intranasally. Measurements and Main Results: Overall, 77% of volunteers consistently shed virus. Infection rate, viral loads, disease severity, and safety were similar between cohorts and were unrelated to quantity of RSV received. Symptoms began near the time of initial viral detection, peaked in severity near when viral load peaked, and subsided as viral loads (measured by real-time polymerase chain reaction) slowly declined. Viral loads correlated significantly with intranasal proinflammatory cytokine concentrations (IL-6 and IL-8). Increased viral load correlated consistently with increases in multiple different disease measurements (symptoms, physical examination, and amount of nasal mucus). Conclusions: Viral load appears to drive disease manifestations in humans with RSV infection. The observed parallel viral and disease kinetics support a potential clinical benefit of RSV antivirals. This reproducible model facilitates the development of future RSV therapeutics.